Pengaruh Kualitas Produk, Harga dan Promosi Terhadap Keputusan Pembelian Jamu Sabdo Palon Di Sukoharjo (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2022)
This study aims to obtain empirical evidence that partially product quality has a significant positive effect on consumer purchasing decisions of Sabdo Palon traditional herbal syrup in Sukoharjo district and obtain empirical evidence that product quality, price and promotion together have a significant effect on decision to buy traditional herbal syrup Sabdo Palon in Sukoharjo. In this research, the sampling technique that the writer use is a non probability sampling. The method that used in sampling is non-probability sampling, that is the sampling was not choosen randomly. The type of sampling used in this research is purposive sampling. The sample used in this research amounted to 100 consumers of traditional herbal syrup Sabdo Palon in Sukoharjo, data collection in this research using a questionnaire. The data analysis technique used is validity test, reliability test, classical assumption test and hypothesis test using SPSS version 16.00. The research show the product quality variable has a positive effect on purchasing decisions with a t value of 4.562 and a significance of 0.000, the price variable does not have a significant effect on purchasing decisions with a t value of -1.892 and a significance of 0.062, the promotion variable has no significant effect on purchasing decisions. with the t value of -1.07 and a significance of 0.915. And the results of this study indicate that the variable product quality, price and promotion together (simultaneously) on purchasing decisions with a significance value of 0.000.